2013
DOI: 10.1021/am403207w
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Resistance and Permselectivity Tradeoffs in Anion Exchange Membranes

Abstract: Salinity gradient energy technologies, such as reverse electrodialysis (RED) and capacitive mixing based on Donnan potential (Capmix CDP), could help address the global need for noncarbon-based energy. Anion exchange membranes (AEMs) are a key component in these systems, and improved AEMs are needed in order to optimize and extend salinity gradient energy technologies. We measured ionic resistance and permselectivity properties of quaternary ammonium-functionalized AEMs based on poly(sulfone) and poly(phenylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
239
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(259 citation statements)
references
References 54 publications
5
239
0
Order By: Relevance
“…In our treatment of IEMs we also neglect water transport through them, as well as their resistance. In reality it is known that IEM permselectivity and resistance are coupled and depend on thickness, swelling, 59 and solution concentration. 60,61 Though incorporating detailed IEM properties is clearly important to obtain agreement between theoretical predications and experimental results when using particular IEMs, we consider ideally permselective IEMs to focus on the "best case" scenario of IEM performance among all cell architectures that we consider.…”
Section: Modeled Systemmentioning
confidence: 99%
“…In our treatment of IEMs we also neglect water transport through them, as well as their resistance. In reality it is known that IEM permselectivity and resistance are coupled and depend on thickness, swelling, 59 and solution concentration. 60,61 Though incorporating detailed IEM properties is clearly important to obtain agreement between theoretical predications and experimental results when using particular IEMs, we consider ideally permselective IEMs to focus on the "best case" scenario of IEM performance among all cell architectures that we consider.…”
Section: Modeled Systemmentioning
confidence: 99%
“…It has been demonstrated that high solution concentrations suppress the Donnan exclusion capacity of the ion exchange membranes, severely reducing the permselectivity and diminishing energy conversion efficiency in a RED stack [25,35]. An increase in the concentration of charged groups in the membranes may improve the ion exchange capacity, but other factors (e.g, electrical resistance, swelling degree, permselectivity, and mechanical strength) should also be taken into account [13,36,37].…”
Section: Influence Of Hc Solution Concentrationmentioning
confidence: 99%
“…However, membrane ionic resistance is a parameter that is highly related to membrane thickness, i.e., reduction of the IEM thickness results in the decrease of ionic (area) resistance [32,65]. Intrinsic ionic resistance was introduced in order to exclude the membrane thickness effect and directly compare the intrinsic membrane properties with different thicknesses.…”
Section: Electrochemical Properties Of Membranesmentioning
confidence: 99%
“…Intrinsic ionic resistance was introduced in order to exclude the membrane thickness effect and directly compare the intrinsic membrane properties with different thicknesses. Intrinsic ionic resistance is a membrane intrinsic property that is obtained from dividing the ionic resistance by the membrane thickness [65]. The change of membrane intrinsic resistance with O-MWCNT loading is shown in Fig.…”
Section: Electrochemical Properties Of Membranesmentioning
confidence: 99%